Предмет: Математика,
автор: aldi9idirov
Разложить на множители многочлен: x²-xy+x-xy²+y³-y²
aldi9idirov:
Пожалуйста
Ответы
Автор ответа:
1
x²-xy+x-xy²+y³-y² = (x²-xy+x)-(xy²-y³+y²) = х(х-у+1) - у²(х-у+1) = (х-у+1)(х-у²).
Автор ответа:
0
Ответ:
x²-xy+x-xy²+y³-y² = (x²-xy+x)-(xy²-y³+y²) =х*(х-у+1)-у²*(х-у+1)=(х-у+1)*(х-у²)
Похожие вопросы
Предмет: Немецкий язык,
автор: Ника2513
Предмет: Русский язык,
автор: НастанаСластёна
Предмет: Русский язык,
автор: луна73
Предмет: Алгебра,
автор: lizamarkiza11
Предмет: Українська мова,
автор: dianakotenko7